2021
DOI: 10.3390/su13126854
|View full text |Cite
|
Sign up to set email alerts
|

Government Environmental Information Disclosure and Environmental Performance: Evidence from China

Abstract: Government environmental information disclosure (GEID) is a key policy instrument in environmental governance. Local governments in China are improving the disclosure level of environmental information, but does the environmental information disclosed by local governments reflect the existing state of the local ecological environment? This paper analyzes the correlation between GEID and environmental performance and verifies whether or not the environmental information disclosed by local governments can reflec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…The green development of enterprises belongs to the category of green development, but the main body is enterprises. Therefore, it has the general characteristics of green development and has the characteristics of maintaining the unique green development of enterprises [ 4 ].…”
Section: Concept Definition and Theoretical Basismentioning
confidence: 99%
See 1 more Smart Citation
“…The green development of enterprises belongs to the category of green development, but the main body is enterprises. Therefore, it has the general characteristics of green development and has the characteristics of maintaining the unique green development of enterprises [ 4 ].…”
Section: Concept Definition and Theoretical Basismentioning
confidence: 99%
“…erefore, it has the general characteristics of green development and has the characteristics of maintaining the unique green development of enterprises [4].…”
Section: Concept Definition and Theoretical Basismentioning
confidence: 99%
“…The PITI report was released by IPE, a well-known environmental organization, as the participation of environmental organizations can effectively reduce pollutant emissions [36]. After considering the addition of 7 cities in 2013, this conclusion still holds [16,37]. The most feasible approaches for public participation involve curbing pollutant emissions and improving environmental technology efficiency [38].…”
Section: Environmental Performance Of Public Participationmentioning
confidence: 99%
“…In the process of rural environmental governance, government environmental information disclosure plays an important role. Some scholars have used empirical evidence to prove that the disclosure of government environmental information reflects local environmental performance and improves the effectiveness of government environmental governance decisions [14,15]. When specific to a particular environmental field, some scholars found that information disclosure effectively reduces the concealment and underreporting of air pollution by innovatively examining the impact of environmental information disclosure on government air pollution control [16,17].…”
Section: Environmental Information Disclosurementioning
confidence: 99%